PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN PEMAHAMAN MAHASISWA PADA MATA KULIAH KIMIA DASAR PROGRAM STUDI PENDIDIKAN MATEMATIKA - Yulianti, Eni (MAT-EDUKASIA, 2019)
The activities of study proces is the main activity in the lecture. The success of the lectures will be achieved if active learning activities. Active learning activities require students actively involved in learning. Therefore, the purpose of this research is to increase the activ ity of students and student's understanding of mathematics on basic chemistry courses through the application of problem based learning. The subjects of these studies amounted to 16 people. The data in this study was obtained by observation and tests. The results of this study indicate that the application of problem based learning can increase activity of students of 27.6%, of the criteria enough active being active. Understanding of students on the basic chemical courses also increased by 41%, from 44 percentage of learning completeness 41 % to 85%.